Association of IL18 gene polymorphisms (positions -656 G/T, -137 G/C and +105A/C) with Kala-Azar - Yaser Mansoori; Ali Moravej; Sohrab Najafipour; Seyed Amin Kouhpayeh; Mohammad Hasan Meshkibaf; Abbas Abdollahi; Manochehr Rasouli; Ghader Allahverdi (Fasa University of Medical Sciences, 2012)
Background & Objective: Host resistance to Leishmania infection is mediated by cellular immune responses leading to macrophage activation and parasite killing. IL-18 known as interferon-γ inducing factor, stimulate IFN-γ production by T-cells. According to the important role of IL-18 in defense against VL and known effect of IL-18 gene polymorphisms on its production, the aim of this study was to investigate the probable relation between IL-18 gene polymorphisms and susceptibility to VL in Iranian patients. Materials & Methods: The study groups included 118 pediatric patients suffered from VL and 156 non-relative healthy persons from the same endemic area as the patients. In both study groups IL-18 gene polymorphisms at positions -656 G/T, -137 G/C and +105A/C (codon 35/3) were analyzed by PCR-RFLP (Polymerase Chain Reaction - Restriction Fregment Length Polymorphism). Results: The result showed that the frequency of T allele at position -656 was significantly higher in the controls compared to that in the patients (P=0.047). But in none of the genotypes of IL-18 there was significant difference between patients and controls. In addition, the distribution of ATG haplotype and AGG/ATG haplo-genotype were significantly higher in the controls compared to that in patients with VL (P=0.043and P=0.044, respectively). Furthermore a strong LDs (P<0.001) were detected between the -607, -137 and codon 35/3 SNPs. Conclusion: In conclusion, this study showed that the frequency of T allele at position -656 and ATG haplotype and AGG/ATG haplogenotype (positions +105, -656 and -137) were significantly higher in the controls. To the best of our knowledge no study has been conducted on IL-18 gene polymorphisms and VL in other countries, therefore, we were not able to compare our results with other investigations, so it seems that more researches in this field on other populations will be worthy.